Nachbildungen von ›originalen‹ Tanagrafiguren der Kunsthandlung Fritz Gurlitt, Berlin 1882-1886 - Jutta Fischer (Les Carnets de l’ACoSt)
From 1881 to 1886 the Berlin art dealer Fritz Gurlitt offered for sale replicas of the so-called Tanagra figurines that were handmade and colored copies of terracottas in the museums of Berlin, Paris, London, and St. Petersburg. Thirty of these figurines are still preserved in the Archaeological Collection of the University of Rostock. The current exhibition “Echt Antik! Terrakotten für Salon und Museum” at the German Amber Museum (Deutsches Bernsteinmuseum) in Ribnitz-Damgarten presents these figurines and traces their journey from the excavations at Tanagra to their reproduction for the bourgeois salon (http://www.deutsches-bernsteinmuseum.de/sonderausstellungen.html).